Asymmetric effects of monetary policy over bull and bear stock market cycles in selected Asean countries - Zare, Roohollah (2014)
The asymmetric impact of monetary policy on real economy is widely accepted in recent years and has been an important topic for macroeconomic policy. Asymmetries in the context of monetary policy refer to the situations in which the impact of a given policy is not constant but varies depending on the circumstances. This study examines the asymmetric response of real output, stock returns and volatilities to monetary policy over bull and bear stock market regimes. This investigation is of great interest for monetary policy makers to implement effective policy decisions and for financial markets participants to formulate successful investment and risk management decisions. This study examines asymmetries using the pooled mean group (PMG) technique of Pesaran et al. (1999). Bull and bear phases are identified by employing two approaches: the Markov-switching models and the non-parametric approach proposed by Pagan and Sossounov (2003). The empirical results from the panel of the ASEAN5 countries (Malaysia, Indonesia, Singapore, the Philippines and Thailand) for the period 1991:1-2011:12, show that the long-run response of real output, stock returns and volatilities to monetary policy is statistically stronger over bear markets than bulls providing evidences to support the prediction of finance constraints models. Accordingly, policy makers should consider the bull and bear regimes while implementing monetary policies and condition the size of the shifts in policy rate to the specific phase of the stock market at the time of policy implementation. Failing to consider stock market conditions at the time of policy implementation may not have proper impact for stabilizing the stock market. Moreover, stock market investors should not only pay close attention to the development of monetary policy, but also to the specific stock market regime at the time of investment decisions. The empirical results of this study also indicate that increase in the policy rate (restrictive monetary policy) leads to decrease in real output in the long-run, no matter if the stock market is in a bull or bear state. The PMG estimation results also indicate that positive changes in short-term interest rate have negative long-run effect on stock returns as predicted by the asset pricing theories. The empirical results from the PMG estimation of the response of stock market volatility to monetary policy show that increase in the policy rate raises stock market volatility in the long-run. This positive relation can be explained by the “leverage effect” which refers to the asymmetric relationship between stock market returns and volatility.